Why it is often underestimated: Historical Study of Ammonia Gas Exposure Impacts towards Human Health - Diana Mutia Pratiwi; Roekmijati Widaningroem Soemantodjo; Suyud Warno Utomo (E3S Web of Conferences, 2018)
Ammonia is one of the major pollutants in the air that easily recognized with its pungent odor, and harmful when it exposed to the human. Exposure to the released ammonia gas potentially froze all the contacted tissue, and irritations to the skin, eyes, respiratory tract, and lungs. However, due to the lack of scientific belief of carcinogenic issues for human health, exposure to the ammonia often underestimated. This study will focus on analyzing the possibility of long-term impacts towards human based on the related case of accidental or non-accidental exposure of ammonia, from the causative factors, the concentration level of gas exposure, and its impact. This study uses a narrative review based on the record of cases, and questionnaire to the workers at urea fertilizer company X. From the study of the previous similar cases, it can be inferred that short-term exposure to ammonia is proven to irritate and burns to the moisture tissue and respiratory system that able to recover with immediate treatment. Long-term exposure of ammonia did not cause a specific carcinogenic disease, but in some cases can cause a permanent burn injury, unusual habit in breathe, and in special case can cause a brain related disease.